Afterword: Media Sport — Coming to a Screen near and on You. Issue 1 (May 2015) - Rowe, David
The complex, often unpredictable and shifting media sport landscape demands a reinvigorated concern with consumption and innovation. But it also must embrace production, adaptation, resistance, reproduction, and the exercise of power – as well as pleasure, identity and strategic citizen mobilisation. This theme section exemplifies these tensions between change and continuity, and the purpose of this article is to provide further observation on the themes and issues that have emerged through the various articles in the issue.